The effectiveness of tarbiyah halaqoh activities on teacher performance in improving Islamic Religious understanding at YPI Nurul Fikri Suka Makmur, Binjai District, Langkat Regency - Azmy Azmy; Alfian Tanjung; Fenny Mustika Piliang (Indonesian Journal Education, 2026)
This study aims to analyze the effectiveness of tarbiyah halaqoh activities in improving teacher performance in strengthening Islamic religious understanding at YPI Nurul Fikri Suka Makmur, Binjai District, Langkat Regency. The research employed a quantitative correlational design involving all 30 teachers as the sample. Data were collected using questionnaires and analyzed through normality, linearity, homogeneity, Product Moment correlation, and t-tests. The findings indicate that tarbiyah halaqoh activities are categorized as good, with a mean score of 61.53, while teacher performance in enhancing Islamic religious understanding is also classified as good, with a mean score of 67.66. Statistical analysis reveals a very strong positive correlation between tarbiyah halaqoh activities and teacher performance (r = 0.90 more than r table = 0.80). The t-test result (t = 25.1 more than 1.31; ? = 0.05) confirms that the alternative hypothesis is accepted. These results demonstrate that tarbiyah halaqoh activities significantly and directly contribute to improving teacher performance in developing Islamic religious understanding.